Impact of Financial Development on Greenhouse Gas Emissions in Indonesia: A Comprehensive Analysis (2000-2019) - Yudaruddin, Rizky; Hafsari, Pebiansyah; Suharsono, Suharsono; Budiman, Puput Wahyu; Purnomo, Adi Hendro; Nugroho, Bramantyo Adi; Adi, Ari Sasmoko (International Journal of Energy Economics and Policy, 2023)
This study aims to comprehensively analyze the impact of financial development on greenhouse gas emissions in Indonesia during the period from 2000 to 2019. Using ordinary least squares with robust standard errors, the study revealed a positive and significant relationship between financial development and total greenhouse gas emissions. The study revealed a positive and significant relationship between financial development and total greenhouse gas emissions by employing utilizing a comprehensive financial development index. The findings indicate that higher levels of financial development by employing utilizing a comprehensive financial development index led to increased greenhouse gas emissions. Moreover, sector-specific analyses demonstrated that financial development significantly and positively influences emissions across various sectors, including the energy sector, agriculture, forest, and other land uses, peatland fires, and waste. However, intriguingly, financial development was found to have a significant and negative impact on greenhouse gas emissions in the industrial processes and product use sector, suggesting its role in promoting sustainable practices and contributing to emissions reduction in this specific domain.